"There are ways … drug companies will get into DTC decisions": How Australian drug and therapeutics committees address pharmaceutical industry influence. Issue 5 (26th November 2020) - Parker, Lisa; Bennett, Alexandra; Mintzes, Barbara; Grundy, Quinn; Fabbri, Alice; Karanges, Emily A.; Bero, Lisa
Abstract : Aims: One tool for protecting quality use of medicines in hospitals is a drug and therapeutics committee (DTC) that oversees medicines availability. Pharmaceutical industry marketing to prescribers is associated with less appropriate prescribing and increased costs. There is little data on decision‐making practices of DTCs so it is unknown whether or how they might be vulnerable to pharmaceutical industry influence. This project explores DTC decision‐making with a focus on how pharmaceutical industry influence on access and use of medicines is identified and managed. Methods: We used a qualitative methodology with individual interviews of 29 participants who were current or recent members of public hospital DTCs across New South Wales, Australia. Participants included medical, pharmacy and nursing staff and 1 citizen. Committees were linked to specific hospitals or regions, and some were affiliated with paediatric, neonatal, rural or mental health services. Results: Drug committee processes for oversight of medicines in public hospitals are vulnerable to pharmaceutical industry influence at several points. Applications for formulary additions are sometimes initiated and completed by company representatives. Conflict of interest disclosures among applicants and committee members may be incomplete. In some institutions, medicines are available from pharmaceutical companies without committee review, including through free samples and industry‐supported medicines access programmes. Participants noticed the presence and impact of pharmaceutical company marketing activities to local clinicians, resulting in increased prescriber demand for products. Conclusion: Improved DTC practices and review of hospital policies concerning pharmaceutical marketing activities might preserve the independence of evidence‐based decision‐making for safe, cost‐effective prescribing.